Deformation and damage evolution of rock salt under multilevel cyclic loading with constant stress intervals. (1st February 2022) - Zhao, Kai; Ma, Hongling; Li, Yinping; Li, Peng; Dong, Zhikai; Liu, Xin; Yin, Hongwu; Yang, Chunhe; Chen, Xiangsheng
Highlights: Multilevel cyclic loading tests with constant stress intervals are conducted on rock salt. The overall stress–strain curves and irreversible deformation are investigated. The constant stress interval in cyclic loading induces the advance of the dilatancy point. Damage evolution behavior at each loading stage is quantitatively analyzed. Abstract: The rocks surrounding a salt cavern used as a compressed air energy storage (CAES) system experience cyclic internal pressure with intermittent intervals. The operational internal pressures of the salt cavern vary with the geological conditions and electricity generation requirements. In this study, multilevel cyclic loading tests were conducted on rock salt, and the loading waveform included a constant stress interval between each loading–unloading cycle. The deformation and damage evolution at each loading level were investigated. An improved Chaboche fatigue damage model was developed to illustrate the damage accumulation at each loading stage, which considered the effect of damage accumulation during the hold time stage. The results indicated that the deformation generally increased with increasing loading stress levels and exhibited a two-stage variation trend at each loading stage. The longer interval duration per cycle led to an increase in the width and area of the hysteresis loops and the advance of the dilatancy point. The damage variable gradually increased with the loading level. The damage accumulation at each loading level generally exhibited two stages: a rapid increase followed by a stable increase, which matches significantly with the enhanced damage model for the entire loading procedure. This study provides a reference for investigating the deformation and damage properties of other rocks under multilevel fatigue loading and provides guidance for designing the operation pressure of salt caverns in a CAES system.